EVALUATION OF THE PROPERTIES OF LASER BEAM WELDING PROCESS - Babu R, Mohan; S. , Suresh Kumar (International Journal of Psychosocial Rehabilitation, 2020)
This article is all about evaluating the laser beam welding process using the stainless steel samples using the recent mechanical testing methods. Here firstly the stainless steel workpieces (SS304 & SS410) are cut to the required dimension of 8 cm width * 15 cm length * 4 mm thickness. Then the cut workpieces are welded using the laser beam welding machine on both the top and bottom layers, respectively. After being welded, the samples are tested with mechanical testing methods like bending tests, tensile tests, etc. Then finally, the results are taken from the test, and they are to find the properties of the laser beam welding process.